Novel Mutations in the GTPBP3 Gene for Mitochondrial Disease and Characteristics of Related Phenotypic Spectrum: The First Three Cases From China - Yan, Hui-ming; Liu, Zhi-mei; Cao, Bei; Zhang, Victor Wei; He, Yi-duo; Jia, Zheng-jun; Xi, Hui; Liu, Jing; Fang, Fang; Wang, Hua (Frontiers in Genetics, 2021)
Combined Oxidative Phosphorylation Deficiency 23 (COXPD23) caused by mutations in GTPBP3 gene is a rare mitochondrial disease and this disorder identified from the Chinese population has not been described thus far. Here, we report a case series of three patients with COXPD23 caused by GTPBP3 mutations from severe to mild phenotype. The main clinical features of these patients including lactic acidosis, myocardial damage and neurologic symptoms. Whole genome sequencing and targeted panels of candidate human mitochondrial genome revealed that the Patient #1 was a compound heterozygote with novel mutations c.413C>T (p. A138V) and c.509_510del (p. E170Gfs*42) in GTPBP3. Patient #2 was a compound heterozygote with novel mutations c.544G>T (p. G182X) and c.785A>C (p.Q262P), while Patient #3 was a compound heterozygote with a previously reported mutation c.424G>A (p.E142K) and novel mutation c.785A>C (p.Q262P). In conclusion, we firstly describe three Chinese individuals with COXPD23, and discuss the genotype-phenotype correlations of GTPBP3 mutations. Our findings provide novel information in the diagnosis and genetic counselling of patients with mitochondrial disease.